Pengembangan soal literasi matematika konteks pinjaman online untuk siswa SMA - Syah, Muhammad Ferdian; Hasyim, A. Wahid; Verdiansah, Ahmad Ilham (Maliki Interdisciplinary Journal, 2026)
This study aims to develop a mathematical literacy instrument based on the context of online loans for high school students. The development was conducted using a 4D model limited to three stages: define, design, and development due to time constraints. In the define stage, information was obtained that students still experience difficulties in understanding the numerical information displayed on online loan services, such as loan principal, interest, admin fees, monthly installments, and tenor. This condition indicates the need for an assessment instrument that can link mathematical concepts to real-world problems often encountered by students when using legal and illegal online loan services. The design stage focused on developing a question grid that included mathematical literacy competencies, literacy levels 1 to 6, and ability indicators that align with the characteristics of interest calculations, service fees, and risk analysis of online loans. The questions were designed to encourage students’ abilities in formulating, using, and interpreting mathematics through authentic online loan situations. In the development stage, question drafts were prepared and validated by experts to produce an instrument that met the aspects of content, construction, language, and readability. The results indicate that this instrument is suitable for use as a measure of mathematical literacy in the context of online loans.